A human induced pluripotent stem cell‐based modular platform to challenge sensorineural hearing loss. (8th February 2021) - Zine, Azel; Messat, Yassine; Fritzsch, Bernd
Abstract: The sense of hearing depends on a specialized sensory organ in the inner ear, called the cochlea, which contains the auditory hair cells (HCs). Noise trauma, infections, genetic factors, side effects of ototoxic drugs (ie, some antibiotics and chemotherapeutics), or simply aging lead to the loss of HCs and their associated primary neurons. This results in irreversible sensorineural hearing loss (SNHL) as in mammals, including humans; the inner ear lacks the capacity to regenerate HCs and spiral ganglion neurons. SNHL is a major global health problem affecting millions of people worldwide and provides a growing concern in the aging population. To date, treatment options are limited to hearing aids and cochlear implants. A major bottleneck for development of new therapies for SNHL is associated to the lack of human otic cell bioassays. Human induced pluripotent stem cells (hiPSCs) can be induced in two‐dimensional and three‐dimensional otic cells in vitro models that can generate inner ear progenitors and sensory HCs and could be a promising preclinical platform from which to work toward restoring SNHL. We review the potential applications of hiPSCs in the various biological approaches, including disease modeling, bioengineering, drug testing, and autologous stem cell based‐cell therapy, that offer opportunities to understand the pathogenic mechanisms of SNHL and identify novel therapeutic strategies. Abstract : Schematic of the various applications of induced pluripotent stem cell (IPSC) modular platform to challenge sensorineural hearing loss. IPSCs can be generated via genetic reprogramming of somatic cells from patient/healthy subject. In the inner ear, this technology has emerged as a promising tool for disease modeling, bioengineering, drug screening/validation and as an otic sensory progenitor source for autologous sensory cell replacement. In the cochlear epithelium, inner hair cells are arranged in a single row and outer hair cells are arranged in three rows (blue color). The supporting cells (yellow color) surround the sensory hair cells (HC).